2008
DOI: 10.1161/circulationaha.108.778795
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Murine Cardiac Myocytes From Induced Pluripotent Stem Cells

Abstract: Background-The recent breakthrough in the generation of induced pluripotent stem (iPS) cells, which are almost indistinguishable from embryonic stem (ES) cells, facilitates the generation of murine disease-and human patientspecific stem cell lines. The aim of this study was to characterize the cardiac differentiation potential of a murine iPS cell clone in comparison to a well-established murine ES cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
305
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(320 citation statements)
references
References 29 publications
9
305
2
4
Order By: Relevance
“…Considering the prominent role of Ca 2+ as a cellular second messenger in directing the fate of stem cells towards cardiac [19][20][21]. We postulated that one of the critical targets f o r i n d u c t i o n o f [ C a 2 + ] i s i g n a l i n g i n v o l v e d i n cardiomyogenesis could be the activation of purinergic receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the prominent role of Ca 2+ as a cellular second messenger in directing the fate of stem cells towards cardiac [19][20][21]. We postulated that one of the critical targets f o r i n d u c t i o n o f [ C a 2 + ] i s i g n a l i n g i n v o l v e d i n cardiomyogenesis could be the activation of purinergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular [Ca +2 ] i exerts multiple functions in the process of cardiac cell differentiation and early heart development depending upon the amplitude, space, and time of [Ca 2+ ] i signaling. Decoding the molecular mechanism of the multifaceted roles of [Ca 2+ ] i signaling will therefore not only contribute to decipher molecular pathways of cardiogenesis but also help to elaborate protocols for highly efficient cardiomyocyte differentiation from ES cells [18][19][20][21]. During embryonic heart formation, a couple of cardiogenic factors turn on Ca 2+ -dependent signaling pathways in cardiac progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, three independent research groups reported the derivation of cardiomyocytes from murine iPSC using embryoid body-based and monolayer-based differentiation protocols [19][20][21]. Later, the capacity for derivation of cardiomyocyte-like cells was demonstrated with human iPSC generated using the 4-gene system (OCT4, SOX2, NANOG, and LIN28 transgenes) [15] and the three-gene system (OCT4, SOX2, and KLF4) plus a histone deacetylase inhibitor (valproic acid) [23].…”
Section: Brief Historical Overview Of the Attempts To Cultivate Rhythmentioning
confidence: 99%
“…Because of their multilineage differentiation potential, pluripotent stem cells (PSCs), such as embryonic stem cells and iPS cells (vide infra), represent an ideal source from which to obtain CMCs: in fact, embryonic stem cells and iPS cells give rise to all the cell derivatives of the three germ layers (ectoderm, mesoderm and endoderm). [11][12][13] PSCs spontaneously differentiate into CMCs but, unfortunately, the efficiency of this process is extremely low (0.1-1%). Over the last few years, several methods have been proposed to improve the efficiency of this process; 14,15 however, inducing a cardiac fate is still extremely difficult, so easy and reliable approaches for the evaluation of differentiation strategies are needed.…”
Section: The Lvv Systemmentioning
confidence: 99%